Integrating AI and Communication: A Study on Ethical Practices in Halal Supply Chain Management - Jamal Ismail; Abdul Haris Muchtar; Muhammad Irsyad Hanafi; Ahmad Ibnu Affandi; Muhammad Ulil Abshor As Shofy (TechComp Innovations: Journal of Computer Science and Technology, 2024)
This research explores the integration of artificial intelligence (AI) and communication strategies in promoting ethical practices within halal supply chain management. As the global halal market expands, the need for efficient, transparent, and ethically sound supply chains becomes critical. This study investigates how AI technologies can enhance operational efficiency while ensuring compliance with halal principles, and examines the role of effective communication in fostering stakeholder engagement and building consumer trust. Utilizing a mixed-methods approach that includes literature review and qualitative case studies, the research identifies key ethical challenges associated with AI, such as algorithmic bias and data privacy, while highlighting best communication practices to ensure transparency regarding halal compliance. The findings indicate that a synergistic approach combining AI-driven efficiencies with robust communication frameworks can significantly enhance the integrity and transparency of halal supply chains, offering actionable recommendations for businesses aiming to navigate the complexities of AI integration while upholding halal values.